Indigenous sovereignty and the new developmentalism in plurinational Bolivia. (March 2019) - Postero, Nancy; Fabricant, Nicole
Across Latin America indigenous groups are asserting an alternative form of sovereignty they are calling indigenous autonomy. They have found support in international documents such as the 2007 United Nations Declaration of Indigenous Rights, as well as some Left-leaning governments such as those in Bolivia and Ecuador. Yet, there is a fundamental paradox at play in these demands: indigenous actors must negotiate their self-determination with the states whose essential characteristic is exerting territorial sovereignty. In this paper, we consider the politics entailed in managing these difficult political struggles. We examine one lowland indigenous community, the Guaraní of Charagua, Bolivia, which has articulated a vision of indigenous self-determination based in ñandereku, or 'our way of being' in the world. Rather than a liberal notion of territorial administration, this understanding of autonomy implies reciprocal relations between people and the land. We show how the Guaraní must negotiate the 'spaces in-between' competing notions of state and local sovereignty to approach their vision of self-determination. We argue that their efforts to assert indigenous autonomy can act as a form of emancipatory 'politics, ' but that they are entangled with the 'policing' of the state, requiring skillful negotiations. Thus, their alternative notions of sovereignty must, at times, be smuggled in under the cover of other seemingly shared agendas such as economic development or liberalism. Here, we dispute Rancière's notion of politics as the result of radical disagreement. We show instead how political actors negotiate ambiguities inherent in the multiple meanings of sovereignty to promote their own indigenous visions of self-governance. Thus, we posit that politics does not always require radical ruptures, but instead can emerge from productive entanglements in the 'third spaces' between neighbors, government entities, and worldviews. We conclude that this sort of balancing act might best be understood through the indigenous idea of ch'ixi, the holding in tension of competing but complementary elements.